2020
DOI: 10.1080/23322039.2020.1783909
|View full text |Cite
|
Sign up to set email alerts
|

Commercialization of Moringa: Evidence from Southern Ethiopia

Abstract: The policies in Ethiopia to advance the commercial orientation of farmers need identification of challenges at farmer level and exhaustive actions to shift the farm sector. Further activities have to be done to change the country's present subsistence-oriented farm production system of different crops. The research has aimed at investigating factors determining the Moringa commercialization in southern Ethiopia. The cross-sectional survey method was used to identify 232 Moringa producing smallholder farmers fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…The most used econometric analytical techniques in the analysis of crop market participation include Tobit models, doublehurdle models, and Heckman sample selection models (Donkor et al, 2018;Chen et al, 2020;Tafesse et al, 2020). The Heckman approach is more suitable for incidental truncation where the unobserved values are represented by the zeros; for instance, in situations of wage rate models where the unemployed people are included in the sample (Heckman, 1976;Cameron and Trivedi, 2005).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The most used econometric analytical techniques in the analysis of crop market participation include Tobit models, doublehurdle models, and Heckman sample selection models (Donkor et al, 2018;Chen et al, 2020;Tafesse et al, 2020). The Heckman approach is more suitable for incidental truncation where the unobserved values are represented by the zeros; for instance, in situations of wage rate models where the unemployed people are included in the sample (Heckman, 1976;Cameron and Trivedi, 2005).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The dependent variable was farmers' commercialisation of agricultural produce and it was measured by ACI. The independent variables were chosen from relevant literature (Cazzuffi et al ., 2020; Hoang, 2022; Ogutu and Qaim, 2019; Rubhara and Mudhara, 2019; Tafesse et al ., 2020; Tipraqsa and Schreinemachers, 2009; Truong, 2009) and based on the main characteristics of farmers in the study region. Table 1 describes hypothesised dependent and independent variables in farmers' commercialisation of agricultural produce.…”
Section: Methodsmentioning
confidence: 99%
“…Some regions may have well-developed informal educational system. In a research by Tafesse et al . (2020), the author found that family size had a positive impact on farmers' commercialisation of agricultural produce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations